ANALISIS UPAYA PENINGKATAN PENDAPATAN ASLI DAERAH DALAM RANGKA MENINGKATKAN RASIO KEMANDIRIAN DAERAH (STUDI KASUS PADA PEMERINTAH KABUPATEN/KOTA DALAM PROVINSI JAMBI TAHUN ANGGARAN 2015) - Fathiyah Fathiyah (Universitas Batanghari Jambi, 2016)
This study aims to analyse the efforts made the Government District/Town in Jambi province in an attempt to increase revenue of the original area (PAD) in order to increase the ratio of the independence area for fiscal year 2015. These studies are qualitative and quantitative by using the related literature and data Report realization of Budget the county or city within Jambi province fiscal year 2015.Based on the results of the analysis of the obtained conclusions that the ratio of independence County or city within Jambi province are still very small with an overall average of 8.83% just so is need for efforts of local governments to increase the PAD in order to increase the ratio of independence. As for the effort to be made to increase the number of PAD that is by calculating the potential of existing PAD then conducted analysis with micro and macro base it can be done working with related institutions of study so that potential data obtained more accurate PAD. Other efforts is to improve the system of revenue management areas include (1) the expansion of the base of acceptance, (2) control over the revenue leakage, (3) improved the efficiency of the administration of revenue and (4) transparency and accountability. Key word: the original Revenue area, the ratio of Self-sufficiency, the report realization of Budget